1990
DOI: 10.1159/000156508
|View full text |Cite
|
Sign up to set email alerts
|

Vocalizations of Adult Gelada Baboons (Theropithecus gelada): Acoustic Structure and Behavioural Context

Abstract: Vocalizations and accompanying behaviours of adult gelada baboons were studied in four one-male groups kept in large outdoor enclosures in the zoos of Stuttgart and Rheine. Twenty-two acoustically different vocal patterns were determined. According to behavioural context, they were grouped into two categories: (1) contact calls and (2) aggressive and defensive calls. Frequency of calling and the production of different vocalizations were related to social rank and to the age of the sender. Vocalizations in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Thus, even though grunts are typically directed at animals within a unit or bachelor group, unit males frequently hear the grunts of extra-unit males. Furthermore, gelada grunts (figure 1) resemble baboon grunts that are harmonically rich and relatively easy to identify individually (Aich et al 1990;Owren et al 1997;Rendall 2003). For all playback trials, I used a natural sequence of two to four short grunts and one to two prolonged grunts ('prolonged moan'; Aich et al 1990; figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, even though grunts are typically directed at animals within a unit or bachelor group, unit males frequently hear the grunts of extra-unit males. Furthermore, gelada grunts (figure 1) resemble baboon grunts that are harmonically rich and relatively easy to identify individually (Aich et al 1990;Owren et al 1997;Rendall 2003). For all playback trials, I used a natural sequence of two to four short grunts and one to two prolonged grunts ('prolonged moan'; Aich et al 1990; figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, gelada grunts (figure 1) resemble baboon grunts that are harmonically rich and relatively easy to identify individually (Aich et al 1990;Owren et al 1997;Rendall 2003). For all playback trials, I used a natural sequence of two to four short grunts and one to two prolonged grunts ('prolonged moan'; Aich et al 1990; figure 1). Grunt sequences were recorded opportunistically during behavioural observations from less than 7 m using a Sennheiser ME-66 directional microphone and a Marantz PMD 660 digital recorder.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we test Menzerath's law in the vocal communication of wild geladas (Theropithecus gelada), a gregarious primate species with a well-described vocal repertoire, and in which individualstypically adult males-produce long and complex vocal sequences during affiliative contexts (27)(28)(29)(30). The constituent parts of these sequences are discrete, individual calls, and six different call types in total are seen in sequences.…”
Section: Significancementioning
confidence: 99%
“…around the time of ovulation (Saayman 1970;Aich et al 1990;O'Connell and Cowlishaw 1994;Todt et al 1995;Gouzoules et al 1998;. In chacma baboons (Papio ursinus), O'Connell and Cowlishaw (1994) reported that copulation calls were longer in conjunction with full sexual swellings.…”
Section: Variation In Copulation Calls In Relation To Female and Malementioning
confidence: 99%
“…Aich et al 1990;Gouzoules et al 1998). This hypothesis is consistent with the observation that copulation calls are most likely to occur in conjunction with maximum sexual swelling but inconsistent with the observation that calls may occur in any stage of the menstrual cycle and even during pregnancy.…”
Section: Hypothesis 6: Copulation Calls Are Signals With Which Femalementioning
confidence: 99%